A Study on the Role of Religious Organizations in Fostering Intercultural Dialogue and Tolerance in Muslim and Non-Muslim Communities - saputra, dedi (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
This study aims to analyze the role of religious organizations in encouraging intercultural dialogue and tolerance in Muslim and non-Muslim communities. This study uses a qualitative research method with a narrative approach. The type of data collection is carried out in a literature manner by reading books, journals, and other sources that are believed to be true. The data that has been collected is analyzed and interpreted to arrive at the research objectives. The results of the study show that religious organizations function as a bridge of communication between Muslim and non-Muslim communities, by organizing activities such as seminars, workshops, and interfaith meetings. This activity not only enhances intercultural understanding but also strengthens social relationships among community members from different backgrounds. In addition, the study found that challenges faced by religious organizations in facilitating intercultural dialogue include stereotypes, prejudices, and a lack of support from certain parties. However, with an inclusive and collaborative approach, religious organizations can play an important role in creating a harmonious and tolerant environment. The conclusion of this study emphasizes the importance of the active role of religious organizations in promoting intercultural dialogue and tolerance, as well as the need for support from the wider community to achieve these goals. These findings are expected to provide insights for the development of more effective intercultural dialogue strategies in a multicultural society.